Preparation and Characterization of Biodegradable Poly(Lactic Acid)/Tapioca Starch Composites - Mansor, Mohd Khairulniza (2010)
Biodegradable composites of poly(lactic acid) (PLA) and dried tapioca starch were prepared by using melt blending technique with a Haake mixer at 100/0, 90/10, 80/20, 70/30, 60/40 and 50/50 blend ratios. The study on the effect of adding of 1, 3, 5, 8 and 10 wt.% triacetin on the properties of 70/30 PLA/starch was also investigated in order to study the plasticization effect of the triacetin. The mechanical and thermal properties of composites were investigated by using Instron Universal Testing Machine, Fourier Transform Infrared Spectroscopy (FTIR), Differential Scanning Calorimetry (DSC), and Thermogravimetry Analysis (TGA). The morphology of the composites were analysed by Scanning Electron Microscopy (SEM). The tensile strength of PLA/starch composites decreased with the increased of the starch loading. The tensile modulus and the elongation at break results reveal that the composites are stiff and brittle. However, addition of triacetin to the 70/30 PLA/starch composites improve the flexibility of the composites, indicating by the increase in tensile strength and elongation at break at 5 and 8 wt.% respectively. The FTIR spectra of composites showed that there is shifting to lower wavenumber (1750 to 1748 cm-1) for C=O indicating that some interaction occurs between PLA/starch composites with addition of triacetin. The starting decomposition temperature was shifted to lower values as starch and plasticizer were increased in the composites. The glass transition temperature (Tg), cold crystallization temperature (Tcc) and melting point (Tm) of the PLA/starch composites were shifted to lower temperature with the increasing amount of plasticizer. The micrographs show the PLA phase becoming discontinuous as the starch loading increases. The addition of triacetin improves interfacial adhesion between PLA and starch and the composites become more homogenous. The dependence of water uptake on the absorption characteristics of PLA/starch composites was evaluated by immersion in distilled water with respect to starch and triacetin loading. Water absorption increased with increasing of starch loading due to the hyrdophilicity nature of starch. The composites with addition of triacetin give significant change on the water absorption with the increase in the amount of plasticizer. The biodegradability of composites was evaluated by the soil-burial test in 3 months. The rate of degradation increased with the increased amount of starch.